Inflammation and cancer: molecular mechanisms and clinical consequences - Akkız, Hikmet; Şimşek, Halis; Balcı, Deniz; Ülger, Yakup; Onan, Engin; Akçaer, Nevin; Delik, Anıl (Frontiers in Oncology, 2025)
Inflammation, a hallmark of cancer, has been associated with tumor progression, transition into malignant phenotype and efficacy of anticancer treatments in cancer. It affects all stages of cancer, from the initiation of carcinogenesis to metastasis. Chronic inflammation induces immunosup-pression, providing an environment conducive to carcinogenesis, whereas acute inflammation induces an antitumor immune response, leading to tumor suppression. Solid tumors have an inflammatory tumor microenvironment (TME) containing cancer cells, immune cells, stromal cells, and soluble molecules, which plays a key role in tumor progression and therapy response. Both cancer cells and stromal cells in the TME are highly plastic and constantly change their phenotypic and functional properties. Cancer-associated inflammation, the majority of which consists of innate immune cells, plays an important role in cancer cell plasticity, cancer progression and the development of anticancer drug resistance. Today, with the combined used of advanced technologies, such as single-cell RNA sequencing and spatial molecular imaging analysis, the pathways linking chronic inflammation to cancer have been largely elucidated. In this review article, we highlighted the molecular and cellular mechanisms involved in cancer-associated inflammation and its effects on cancer progression and treatment response. We also comprehensively review the mechanisms linking chronic inflammation to cancer in the setting of GI cancers.